Human Breast Milk Enhances Intestinal Mucosal Barrier Function and Innate Immunity in a Healthy Pediatric Human Enteroid Model - Noel, Gaelle; In, Julie G.; Lemme-Dumit, Jose M.; DeVine, Lauren R.; Cole, Robert N.; Guerrerio, Anthony L.; Campbell, James D.; Kovbasnjuk, Olga; Pasetti, Marcela F. (Frontiers in Cell and Developmental Biology, 2021)
Breastfeeding has been associated with long lasting health benefits. Nutrients and bioactive components of human breast milk promote cell growth, immune development, and shield the infant gut from insults and microbial threats. The molecular and cellular events involved in these processes are ill defined. We have established human pediatric enteroids and interrogated maternal milk’s impact on epithelial cell maturation and function in comparison with commercial infant formula. Colostrum applied apically to pediatric enteroid monolayers reduced ion permeability, stimulated epithelial cell differentiation, and enhanced tight junction function by upregulating occludin expression. Breast milk heightened the production of antimicrobial peptide alpha-defensin 5 by goblet and Paneth cells, and modulated cytokine production, which abolished apical release of pro-inflammatory GM-CSF. These attributes were not found in commercial infant formula. Epithelial cells exposed to breast milk elevated apical and intracellular pIgR expression and enabled maternal IgA translocation. Proteomic data revealed a breast milk-induced molecular pattern associated with tissue remodeling and homeostasis. Using a novel ex vivo pediatric enteroid model, we have identified cellular and molecular pathways involved in human milk-mediated improvement of human intestinal physiology and immunity.